Textiles attached to Roman coins: Case studies and interpretations - Morgado-Roncal, Leyre; Grömer, Karina (Archaeological Textiles Review, 2023)
In Roman archaeology of the provinces situated in modern-day Europe, textile studies have been traditionally approached through written and iconographic sources. The archaeological textile corpus in the first half of the first millennium CE is particularly scarce, and often come from old excavations without detailed contexts. Moreover, the findings are difficult to locate in the scientific literature. In the last few decades, Roman period textiles have been studied with an interdisciplinary approach, including fibre or dyestuff analyses and scientific methods. For example, Raman and Surface Enhanced Raman Scattering (SERS), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS) and spectrophotometry. It is also important to study the contexts of the textiles, the graves, settlements and hoards and thereby understand the archaeological textiles in situ. This article provides an overview of a lesser-known phenomenon: textiles attached to Roman coins. It presents evidence of textiles preserved attached to coins in archaeological contexts from the Roman provinces (Hispania, Noricum, and Pannonia). It draws attention to a little studied textile function and compares findings from different regions of the Roman Empire.